The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1051/lait:2003013
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dynamic loop mixer operating conditions for production of O/W emulsion for cell microencapsulation

Abstract: -Emulsification and spray-drying were selected to develop a low-cost cell microencapsulation method adaptable to large-scale production to improve the stability of sensitive probiotic bacteria. The aim of the present study was to determine the optimum operating conditions to produce anhydrous milk fat/whey protein emulsion using a dynamic loop mixer as a first step for the microencapsulation process. The effect of various parameters of the two-phase dispersion process on fat globule size and their distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Picot and Lacroix proposed easy scaled-up and low-cost microencapsulation method to improve the stability of probiotic lactic cultures and to overcome these aforementioned limits. This technique consisted of coating milk fat droplets containing powder particles of freeze-dried bacteria with whey protein polymers, using emulsification and spray drying in a continuous two-step process (Picot and Lacroix, 2003b).…”
Section: Freeze Drying and Spray Dryingmentioning
confidence: 99%
“…Picot and Lacroix proposed easy scaled-up and low-cost microencapsulation method to improve the stability of probiotic lactic cultures and to overcome these aforementioned limits. This technique consisted of coating milk fat droplets containing powder particles of freeze-dried bacteria with whey protein polymers, using emulsification and spray drying in a continuous two-step process (Picot and Lacroix, 2003b).…”
Section: Freeze Drying and Spray Dryingmentioning
confidence: 99%
“…It was reported that the stationary phase cultures are more resistant to heat compare to cells in exponential growth phase [61].One approach used by a number of researchers to improve probiotic survival is the addition of protectants to the media prior to drying. For example, the incorporation of thermoprotectants, such as trehalose [75], non-fat milk solids and/ or adnitol [76], growth promoting factors including various probiotic/prebiotic combinations [77] and granular starch [78] have been shown to improve culture viability during drying and storage [79,80].…”
Section: Spray-dryingmentioning
confidence: 99%
“…Multiphase microcapsules were produced using a continuous 2step process, illustrated in Figure 1, which consisted of (1) preparing an o/w emulsion of AMF containing a suspension of micronized SMP used to replace freeze-dried bacteria in a heat-denatured whey protein solution and (2) spray-drying the emulsion. Preparation of soluble whey protein polymers and emulsification were carried out according to the procedures described by Picot and Lacroix (2003a). Whey protein solution containing 10% (wt/wt) solids was prepared in distilled water and kept overnight at 4°C.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…006, Seepex Inc., Enon, Ohio, U.S.A.) to obtain differ-ent hydrophilic/hydrophobic phase ratios (95/5, 92.5/7.5, and 90/ 10 wt/wt) in the emulsion, for a total flow rate of 30 kg/h in the mixer. In agreement with the optimum homogenization conditions previously determined for the production of fat globules ranging from 10 to 50 m (Picot and Lacroix 2003a), the internal mixing speed was set at 2500 rpm.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
See 1 more Smart Citation